PENERAPAN NILAI-NILAI PANCASILA DALAM MEMBENTUK AKHLAKUL KARIMAH BAGI SISWA KELAS VII SMP AL ISMAILIYAH BERINGIN, TAMBELANGAN, SAMPANG - Fathur Rosi; Ali Nurhadi; Wahidah Wahidah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2025)
The moral crisis among students has become an increasingly worrying issue and has sparked controversy over the effectiveness of character education in schools. In this context, the application of Pancasila values is a strategic alternative (solution) to strengthen good character among students. This study aims to describe the application of Pancasila values in shaping good character among seventh-grade students at Al Ismailiyah Beringin Junior High School, Tambelangan, Sampang. The research approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that the values of Belief in God, Unity, and Social Justice are implemented through civic education, extracurricular activities, and religious routines such as the dhuha prayer, recitation of the Qur'an, and social activities of mutual cooperation. Teacher role modeling, a conducive school environment, and structured coaching programs are the main supporting factors, while the influence of the environment outside school is the main challenge. The consistent application of Pancasila values has been proven to foster discipline, responsibility, and tolerance among students. These findings emphasize the importance of integrating Pancasila values into character education (a national education trend) as an effort to revitalize the morals of the younger generation in order to face complex social changes.